If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(v + 5) = 6v + 14 Reorder the terms: 2(5 + v) = 6v + 14 (5 * 2 + v * 2) = 6v + 14 (10 + 2v) = 6v + 14 Reorder the terms: 10 + 2v = 14 + 6v Solving 10 + 2v = 14 + 6v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-6v' to each side of the equation. 10 + 2v + -6v = 14 + 6v + -6v Combine like terms: 2v + -6v = -4v 10 + -4v = 14 + 6v + -6v Combine like terms: 6v + -6v = 0 10 + -4v = 14 + 0 10 + -4v = 14 Add '-10' to each side of the equation. 10 + -10 + -4v = 14 + -10 Combine like terms: 10 + -10 = 0 0 + -4v = 14 + -10 -4v = 14 + -10 Combine like terms: 14 + -10 = 4 -4v = 4 Divide each side by '-4'. v = -1 Simplifying v = -1
| 10=9x+4-6x | | 3x-9y=15 | | 7t+8(4-3t)= | | 4.7=6.7-0.4x | | 2x+4x-7=23 | | 9c=3 | | (9xy-2x^2)(2x+y)=a | | 4x^2-16x-4=-x^2+3x | | (9xy-2x^2)(2x-y)=a | | 3(4x-5y)+2y= | | 2(5x-4)-10x=6x+3(2x-5) | | 4x+(5x+9)=180 | | 3(x+5)+4(x+2)=21 | | 4.7x+0.7=3.5x+5.5 | | 8(2x-3)+4=68 | | 5(x+1)-3=12 | | -4(x+2)-16=11+1 | | -6(8-11)+3(-1+7)= | | -3x^2+6x^2= | | 5(2p+2)-1=2 | | 71+(6x-7)=180 | | -3x-8+x=-4+x-10 | | 2y-3x^2+6x^2-3y= | | 18-6x=8+4x | | 5q+7=-18 | | 9w-17w=48 | | x^2+8x-20=20 | | 7(m+12)=5m | | 10p=s | | 5x+17+2x=17++4x | | 2b+5+3=10 | | y=x+20 |